Nutritional status of U.S. elite heptathletes 1996 USA Track and Field Development Project Report - Houtkooper, L. B. .; Going, S. B.; Ricketts, J.; Robertson, T. (1996)
The nutritional assessment profiles of these athletes, who were at a low phase in their training cycles, indicated that they are lean and have high levels of total body bone mineral density. The reported dietary intakes for these athletes indicates that all but one athlete had adequate to high intakes of calories, carbohydrate, protein, and fat. The athletes had adequate intakes of most vitamins and minerals with the exception of vitamin E which was low in the dietary intake of all the athletes. Calcium and folate intakes were also low for one athlete. All but one of the athletes had normal iron status, but half of the athletes had prelatent iron deficiency and one was iron deficient. Six of the eight athletes had testosterone/cortisol ratios lower than normal values and creatine kinase levels higher than normal indicating they were probably experiencing higher than normal levels of physiological stress and muscle cell membrane damage. Educational information and individual consultation with each athlete was provided to assist the athletes in improving and maintaining their dietary and nutrient supplement intake with a goal to enhance their nutritional status. A copy of this report is provided for each athlete and her coach.